Meningkatkan Kemampuan Membaca Kata Melalui Metode Word Work Bagi Anak Berkesulitan Belajar Kelas IV SD Negeri 10 Sungai Sapih Padang (Single Subject Research) - TANTI HAYATI (Jurnal Penelitian Pendidikan Khusus, 2015)
ABSTRACT TANTI HAYATI. 2015. "IncreasingReading Ability of the Students with Learning Disabilities to Read Words by Using Workword Method in Class IV of SD Negeri 10 Sungai Sapih Padang. Thesis. Special Education Departement of the Faculty of Education of State University of Padang.This research was derived from the problems found at SD N 10 Sungai Sapih Padang indicating that a student in class IV got difficulties to read words with affixation (prefix, suffix and prefix-sufix). The purpose of this research was to prove whether the use of Wordwork method could improve the ability of the student with learning disabilities to read words in class IV of SD Negeri 10 Sungai Sapih Padang.This was an experimental research which applied Single Subject Research (SSR) method and A-B-A design. The data were analyzed by using visual analysis og grafic. The variable was measured by using frequency technique.In the baseline condition (A1) that consisted of four meetings the student’s, in the intervention condition (B) that consisted of six meeting the student’s, and in the baseline condition (A2) that consisted of tree meetings the student’s. The percentage of data overlapped between baseline condition (A1) and intervention condition (B) was 0%., and between baseline  condition (A2) and the intervention condition (B) was 66,7%. These results indicated that the samller the percentage of the data overlapped. The better the effect of the intervention. Based on these results, it was concluded that the use of Wordwork could increase the ability of the student with learning difficulties to read words in class IV of SD Negeri 10 Sungai Sapih Padang.Keyword: learning disability; Increas; reading ability; wordwork